Navigating the complexity of scaling climate solutions through multi-level pathways: The AICCRA meta framework - Ewell, Hanna; Sartas, Murat; Girvetz, Evan; Ogutu, Liz; Ouedraogo, Mathieu; Kagabo, Desire; Byandaga, Livingstone (2025)
The AICCRA Meta Scaling Framework provides a strategic, adaptable approach for scaling. Developed under the AICCRA program for scaling climate-smart agriculture (CSA) and climate information services (CIS) across its six implementation countries in Africa, it addresses the complexity of scaling by emphasizing technical excellence, demand and investment, and sustained use, while also considering socio-political context, digital readiness, and capable partnerships. Rather than viewing scaling as a linear expansion, the framework supports multi-dimensional pathways that integrate local knowledge, business models, and policy engagement. It encourages responsible, inclusive scaling that moves beyond simple reach metrics to long-term adoption and impact. The case of Ghana’s ‘Smart Seeds’ bundle illustrates this approach, combining improved seed varieties, agronomic training, and climate services to increase yields and farmer adoption. By identifying fit-for-purpose engagements and strengthening institutional capacity as key, AICCRA’s Meta Framework guides country clusters toward sustainable, context-specific agricultural transformation, ultimately contributing to more resilient and equitable food systems across diverse African landscapes.